멀티 리간드의 특이적 상호작용이 입자-세포간 상호작용에 미치는 영향 - 윤정현; 이세영; Yoon, Jung Hyun; Lee, Sei Young (Journal of biomedical engineering research, 2022)
Recent advancement of micro/nano technology enables the development of diverse micro/nano particle-based delivery systems. Due to the multi-functionality and engineerability, particle-based delivery system are expected to be a promising method for delivery to the target cell. Since the particle-based delivery system should be delivered to the various kinds of target cell, including the cardiovascular system, cancer cell etc., it is frequently decorated with multiple kinds of targeting molecule(s) to induce specific interaction to the target cell. The surface decorated molecules interact with the cell surface expressed molecule(s) to specifically form a firm adhesion. Thus, in this study, the probability of adhesion is estimated to predict the possibility to form a firm adhesion for the multi-ligand decorated particle-based delivery system.